Plasma leptin levels and cardiac sympathetic function in patients with obstructive sleep apnoea-hypopnoea syndrome. Issue 5 (1st May 2002) - Shimizu, K; Chin, K; Nakamura, T; Masuzaki, H; Ogawa, Y; Hosokawa, R; Niimi, A; Hattori, N; Nohara, R; Sasayama, S; Nakao, K; Mishima, M; et al.
Abstract : Background: The control of body weight and cardiac sympathetic function in patients with obstructive sleep apnoea-hypopnoea syndrome (OSAHS) are important because both factors have significant effects on the mortality of these patients. It has recently been reported that OSAHS has a significant effect on the secretion of leptin, a hormone involved in the control of body weight and sympathetic nerve activity. In addition to the circadian rhythm of leptin secretion, the effects of one night of treatment with nasal continuous positive airway pressure (nCPAP) and the mechanism of the effects of nCPAP on nocturnal leptin secretion in patients with OSAHS has not yet been elucidated. Methods: Blood samples were obtained at 21.00 hours, 00.00 hours, 03.00 hours, and 06.30 hours from 21 subjects with OSAHS (mean apnoea and hypopnoea index 52.4/h), with and without nCPAP treatment. Iodine-123 (I 123 )-meta-iodobenzylguanidine (MIBG) imaging was used to evaluate myocardial sympathetic function before nCPAP treatment. Results: Plasma leptin reached a peak level at 00:00 hours (p<0.01) in patients with OSAHS, both with and without nCPAP treatment. The first night of nCPAP treatment significantly decreased the plasma leptin levels at 03.00 hours (without nCPAP: mean (SE) 21.6 (4.7) ng/ml; with nCPAP: 19.3 (4.1) ng/ml, p<0.02) and at 06.30 hours (without nCPAP: 17.6 (3.8) ng/ml; with nCPAP: 15.2 (3.2) ng/ml, p<0.01). The magnitude of the decrease in leptin levels after nCPAP treatment was significantly correlated with cardiac sympathetic function measured before nCPAP treatment (p<0.03). Conclusions: Patients with OSAHS undergo nocturnal increases in leptin levels in spite of interruption of sleep due to apnoea and hypopnoea, a trend seen in normal subjects. Plasma leptin levels in patients with OSAHS decreased significantly after the first night of nCPAP treatment. Enhanced cardiac sympathetic function in these patients may contribute to the leptin levels before nCPAP treatment and vice versa.